BIOTROP Taps Into Digital Learning Inovation to Strengthen Student’s Engagement on Merdeka Belajar Program - Imantho, Harry; Imran, Zulhamsyah; Perdinan; Sugiarto, Slamet Widodo; Supriyanto (SEAMEO BIOTROP, 2023)
The COVID-19 pandemic has suddenly forced the world of education to carry out a more massive digital transformation that should meet student’s requirements and strengthen their knowledge, skills and competencies. The digital media developed should facilitate student’s self-learning and freedom to learn (Merdeka Belajar) amidst physical and social interaction limitations. Vocational high school students have special requirements compared to upper secondary school students in terms of soft skills and hard skills education. It is very interesting to provide digital educational media which fits their needs. This study aims to develop an online digital platform in responding to the demand of vocational schools that have joined the SEAMEO BIOTROP SMARTS-BE program since 2015 in applied tropical biology. Since 2015, SEAMEO BIOTROP has provided face-to-face mentoring to vocational high schools spread across 10 provinces in Indonesia. The Expert System for Identifying Pest and Disease on lemon orchard is a digital transformation in the mentoring method while demonstrating a new learning experience educational materials into a web-based digital platform and Android application. This expert system demonstrates the implementation of problem base learning (ProBL) concepts to enrich online learning materials for vocational schools in the age of digital science and education.